The community of the beloved disciple - Brown, Raymond Edward, d. 1988 (New York, NY Paulist, 1979)
Includes bibliographical references and index.
Keywords: Beloved disciple; Bible. N.T. Johannine literature -- criticism, interpretation, etc; Church -- biblical teaching